2008
DOI: 10.1007/s00705-008-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of BF mosaic genomes among HIV-1-infected children from Sao Paulo, Brazil

Abstract: HIV-1 genetic diversity information from a pediatric population is scarce. This study enrolled 128 children living with HIV/AIDS, 103 antiretroviral-treated and 25 naive, from the Sao Paulo metropolitan area. Gag, pol and env regions were amplified, and drug resistance mutations, V3 loop, tropism and viral clades were evaluated. Drug resistance mutations among naïve children infected by vertical transmission were uncommon (4.2%), whereas most ARV-experienced children showed extensive mutation patterns. Clade B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The results presented confirmed that subtype B is still the main HIV-1 variant and concordant with data from other studies on adult and children populations from Brazil [24], [33], [34], [35]. The most remarkable observations in this study are that at least 38.1% of the 42 patients with proviral DNA sequences are infected with HIV-1 BF1 recombinant variants, which is relatively much higher if compared to earlier studies on children and adolescent patients in Brazil [33], [34], [35], [36], [37], [38]. This difference is not surprising, because small fragments from different regions of HIV genomes were characterized in the previous studies while we used larger overlapped fragments to sequence the full-length genome, which undoubtedly provides efficient discrimination of HIV subtypes and the recombinant forms.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented confirmed that subtype B is still the main HIV-1 variant and concordant with data from other studies on adult and children populations from Brazil [24], [33], [34], [35]. The most remarkable observations in this study are that at least 38.1% of the 42 patients with proviral DNA sequences are infected with HIV-1 BF1 recombinant variants, which is relatively much higher if compared to earlier studies on children and adolescent patients in Brazil [33], [34], [35], [36], [37], [38]. This difference is not surprising, because small fragments from different regions of HIV genomes were characterized in the previous studies while we used larger overlapped fragments to sequence the full-length genome, which undoubtedly provides efficient discrimination of HIV subtypes and the recombinant forms.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies from this geographic region have analyzed either env and gag or PR and RT genes [Stefani et al, 2000;Cerqueira et al, 2004;Pereira et al, 2004Pereira et al, , 2006Stefani et al, 2007;Véras et al, 2007;Cardoso et al, 2009]. In this study, as more HIV-1 genes were analyzed, a higher rate of subtype B and F1 recombinant viruses was observed, similar to what has been described in other reports [Guimarã es et al, 2002;Oliveira et al, 2008]. The combined env, gag, PR and RT data presented here show that recombination between subtypes B and F1 occurs frequently in central west Brazil and that these recombinant viruses have been disseminating among heterosexual couples.…”
Section: Discussionsupporting
confidence: 85%
“…In the present work, the prevalence of mutations associated with resistance in PI class, was similar to that found in previous studies. 17 , 21 , 27 , 31 Although only LPV/r and NFV have been used in this population, we observed minor mutations conferring cross-resistance to all antiretroviral drugs in this class, which impairs their use as salvage therapy. 27 , 32…”
Section: Discussionmentioning
confidence: 87%